2017
DOI: 10.1002/open.201700143
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Protonated Guanidine and Guanidine Derivatives with Multiply Deprotonated RNA Probed by Electrospray Ionization and Collisionally Activated Dissociation

Abstract: Interactions of ribonucleic acid (RNA) with guanidine and guanidine derivatives are important features in RNA–protein and RNA–drug binding. Here we have investigated noncovalently bound complexes of an 8‐nucleotide RNA and six different ligands, all of which have a guanidinium moiety, by using electrospray ionization (ESI) and collisionally activated dissociation (CAD) mass spectrometry (MS). The order of complex stability correlated almost linearly with the number of ligand atoms that can potentially be invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 99 publications
2
22
0
2
Order By: Relevance
“…The peptide ligands other than RR showed weaker binding to RNA 1 (Figure S6), and besides fragments from RNA backbone cleavage, CAD also produced free RNA as illustrated for VR in Figure 1b. Just like in our previous study, 35 (M – 4H) 4– RNA ions were not observed in CAD of the complexes with a net charge of −3, consistent with PT from protonated ligand to the RNA prior to ligand dissociation. The collision energy required for 50% ligand dissociation by breaking of noncovalent bonds, E 50 ( nc ), in CAD of the (M + VR – 3H) 3– ions was 36.3 ± 0.1 eV, and the collision energy required for 50% fragment formation by breaking of covalent bonds, E 50 ( c ), was 52.1 ± 0.1 eV.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The peptide ligands other than RR showed weaker binding to RNA 1 (Figure S6), and besides fragments from RNA backbone cleavage, CAD also produced free RNA as illustrated for VR in Figure 1b. Just like in our previous study, 35 (M – 4H) 4– RNA ions were not observed in CAD of the complexes with a net charge of −3, consistent with PT from protonated ligand to the RNA prior to ligand dissociation. The collision energy required for 50% ligand dissociation by breaking of noncovalent bonds, E 50 ( nc ), in CAD of the (M + VR – 3H) 3– ions was 36.3 ± 0.1 eV, and the collision energy required for 50% fragment formation by breaking of covalent bonds, E 50 ( c ), was 52.1 ± 0.1 eV.…”
Section: Resultssupporting
confidence: 88%
“…However, RNAs 1 – 4 could potentially form hairpin structures in the presence of ligands. 35 The CAD experiments were performed over a period of 18 months, and we did not observe any correlation between the order of experiments and the collision energy required for dissociation of the RNA or RNA–ligand complexes. Between 50 and 100 scans were added for each spectrum.…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“… 52 , 54 To test this hypothesis, we isolated the (M – H + 4Na) 2+ ˙ ions (along with the 7.7% (M – 2H + 4Na) 2+ ions from H˙ loss) and subjected them to IRMPD, which is a slow heating method 101 that effects dissociation via the channels of lowest energy. Thus IRMPD generally cleaves noncovalent before covalent bonds, 102 unless the energy required for noncovalent bond cleavage exceeds that for covalent bond cleavage. 53 , 103 Using energies (25% laser power, 180 ms irradiation time) that were sufficient for covalent bond cleavage in 59% of the (M – 2H + 4Na) 2+ ions from ESI and 27% dissociation of the (M + 2H) + ˙ ions from ECD of (M + 2H) 2+ ions resulted in only ∼15% dissociation of the (M – H + 4Na) 2+ ˙/(M – 2H + 4Na) 2+ ions.…”
Section: Resultsmentioning
confidence: 99%